(untitled) (Research, Society and Development, 2021)
Aim: To investigate the clinical condition of women using hormonal contraceptives and who were affected by stroke. Method: Scope review using a search strategy in four databases (Pubmed, CINAHL, Scopus, and Web of Science). The inclusion criteria were: quantitative or qualitative studies, review studies, and gray literature in Portuguese, English, or Spanish in the last 10 years. Editorials and articles that do not answer the guiding question were excluded. The data were shown in the form of tables and categories of analysis that allowed to synthesize the findings narratively. Results: The samples included five articles. Combined oral, combined injectable and emergency contraceptives were the most used, but not always highlighted the dosage, route of use, and time of the previous usage. To evaluation of the woman used scales and physical examination, from admission to rehabilitation. The patients’ survival was high. Conclusion: The stroke in women using contraceptives was as severe as in non-users, and those who used the contraceptive for a shorter time had a less severe stroke.